2012
DOI: 10.1080/13557858.2012.730606
|View full text |Cite
|
Sign up to set email alerts
|

Differences in working conditions and employment arrangements among migrant and non-migrant workers in Europe

Abstract: Migrant workers across Europe are more likely to be exposed to certain working and employment arrangements that may place them at higher risk of future health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 21 publications
3
35
0
2
Order By: Relevance
“…The European Working Conditions Survey (EWCS) found that migrant workers were more likely to be exposed to occupational risk factors such as working at very high speeds and carrying heavy loads,27 which is consistent with the findings of our study. The EWCS analysis did not adjust for job role; therefore, the differences could be due to migrants occupying more hazardous jobs than non-migrants.…”
Section: Discussionsupporting
confidence: 92%
“…The European Working Conditions Survey (EWCS) found that migrant workers were more likely to be exposed to occupational risk factors such as working at very high speeds and carrying heavy loads,27 which is consistent with the findings of our study. The EWCS analysis did not adjust for job role; therefore, the differences could be due to migrants occupying more hazardous jobs than non-migrants.…”
Section: Discussionsupporting
confidence: 92%
“…The following variables (36 items) were therefore selected according to the literature: gender [9]; age (treated as a continuous variable) [13], [40]; education (≤9 years versus >9 years) [41], [42]; employment before injury (yes versus no) [43]; qualified work (professional certification versus no certification) [25]; marital status (living in stable partnership versus alone) [44]; litigation in relation with the accident (yes versus no) [45]; native language (French versus others) [29], [30]; work related injury (yes versus no) [9]; injury severity according to the Abbreviated Injury Scale (AIS), (rank 1 to 5; 6 =  fatal injury) [9], [10], [46], trauma localization (upper limb, lower limb, spine, multiple trauma) [3] and pain [9], [11][13]. Quality of life, which correlates well with self-perception of disability and feeling of recovery [6], [47] was also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…For instance exclusion of non-native workers, a growing segment of the work forces in industrialized countries, may bias a predictive model [27], [29]. It is well known that non-native workers are a vulnerable population and may be at risk of being exposed to adverse working conditions [29], [30]. Therefore, they may have more difficulties returning to work.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, culture was presented as a reason workers fail to challenge hazardous work and to report or seek care for health conditions . A few noted the need to research the role of culture in influencing health and safety behaviors or perceptions . In addition, 24 articles (22%) discussed acculturation, mostly in terms of health and safety risks and responses.…”
Section: Resultsmentioning
confidence: 99%
“…Articles also discussed culture in relation to conceptual or theoretical approaches, research instruments, and sampling methods (eg, using cultural indicators to identify participants) . Some article noted that culture could impact self‐reporting or otherwise impede participants’ discourse …”
Section: Resultsmentioning
confidence: 99%